Antibacterial Activity of Leaf Extracts of Baeckea frutescens against Methicillin-Resistant Staphylococcus aureus - Razmavar, S.; Abdulla, M.A.; Ismail, S.; Hassandarvish, P. (Hindawi Publishing Corporation, 2014)
This study was based on screening antibacterial activity of the ethanol extract of Baeckea frutescens L. against MRSA clinical isolates, analyzes the potential antibacterial compound, and assesses the cytotoxicity effect of the extract in tissue culture. Leaves of Baeckea frutescens L. were shade dried, powdered, and extracted using solvent ethanol. Preliminary phytochemical screening of the crude extracts revealed the presence of alkaloids, flavonoids, steroids, terpenoids, phenols, and carbohydrates. The presence of these bioactive constituents is related to the antibacterial activity of the plant. Disc diffusion method revealed a high degree of activity against microorganisms. The results confirm that Baeckea frutescens L. can be used as a source of drugs to fight infections caused by susceptible bacteria.